A prospective study of maternal factors and perinatal outcome of preterm birth - Dudhrejia, Kavita; Karena, Zalak V.; Patel, Rahul P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preterm birth (PTB) is a leading cause of perinatal morbidity and mortality, henceforth being a major concern for the obstetricians and paediatricians as well being a major health care issue. Preventing and treating the associated risk factors could play a major role in curbing the perinatal morbidity and mortality. Methods: A total 100 women with preterm labour or an indicated preterm termination of pregnancy were enrolled in the study. They were evaluated by history taking, clinical examination, and ultrasonography. Corticosteroids were given to all the patients. Maternal risk factors, obstetric outcome and perinatal outcome till discharge were studied. Results: Of the 100 women studied, mean age of the cases was 27 years, 60% of the cases belonged to lower socio-economic class, 74% of the cases were under 55 kgs weight group and 77% of cases were anaemic. 34% cases were below 34 weeks of gestation, 58% were multigravida, and 2% grand multipara with 35% labour being induced labour because of presence of various risk factors such as preterm premature rupture of membranes (PPROM), pre-eclampsia, eclampsia and chorioamnionitis. 6% cases had multiple pregnancies and 8% had history of preterm delivery in previous pregnancy. Out of 107 babies, 73% neonates required neonatal intensive care unit (NICU) admission and there was 12.14% neonatal mortality rate. Conclusions: Anaemia, malnutrition, infection, high order pregnancy are the preventable causes of preterm birth which can be prevented, screened and treated by specialised antenatal programs.